Multi-attribute aware scheduling for inter-datacenter bulk transfers - Yang-yang LI; Hong-bo WANG; Peng ZHANG; Jian-kang DONG; Shi-duan CHENG (Tongxin xuebao)
A multi-attribute decision making method to schedule inter-datacenter bulk data was proposed.First,hierarchical analysis was used to analyze the dominant relationship among attributes.Based on the relative weights of attributes which were calculated via information entropy,the evaluation to each intermediate data center was provided.Then the multi-attribute aware scheduling problem was modeled on a time expanded graph and formulated as a minimal cost flow problem.Finally,the scheme with general store-and-forward mechanism and single attribute based approach under several different simulation settings was compared.The results demonstrate that our strategy can take multiple attributes into consideration,and can find the bulk transfer route with the best integrated evaluation.